2022
DOI: 10.3390/membranes13010034
|View full text |Cite
|
Sign up to set email alerts
|

Layered Perovskites BaLnnInnO3n+1 (n = 1, 2) for Electrochemical Applications: A Mini Review

Abstract: Modern humanity is facing many challenges, such as declining reserves of fossil energy resources and their increasing prices, climate change and an increase in the number of respiratory diseases including COVID-19. This causes an urgent need to create advanced energy materials and technologies to support the sustainable development of renewable energy systems including hydrogen energy. Layered perovskites have many attractions due to their physical and chemical properties. The structure of such compounds conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…The graphical representation for the samples with nominal compositions SrLa2Sc1.9Gd0.1O7 and SrLa2Sc1.9Ti0.1O7.05 is shown in Figure 3. As previously shown for the bilayer perovskites BaLa2In2O7 and BaNd2In2O7 [42], the donor doping of the indium sublattice is almost non-existent, in contrast to monolayer perovskites. The crystal lattice of bilayer perovskite contains a linkage of two layers of octahedrons in one perovskite layer and is more rigid compared to the monolayer perovskite layered structure where the layers of the perovskite block are one layer of octahedrons.…”
Section: Resultssupporting
confidence: 59%
“…The graphical representation for the samples with nominal compositions SrLa2Sc1.9Gd0.1O7 and SrLa2Sc1.9Ti0.1O7.05 is shown in Figure 3. As previously shown for the bilayer perovskites BaLa2In2O7 and BaNd2In2O7 [42], the donor doping of the indium sublattice is almost non-existent, in contrast to monolayer perovskites. The crystal lattice of bilayer perovskite contains a linkage of two layers of octahedrons in one perovskite layer and is more rigid compared to the monolayer perovskite layered structure where the layers of the perovskite block are one layer of octahedrons.…”
Section: Resultssupporting
confidence: 59%
“…The complex oxides with high temperature protonic conductivity are actively studied due to their potential applications in electrochemical devices such as proton-conducting fuel cells (PCFC) and electrolyzers (PCEC) [1][2][3][4][5][6][7][8]. The design and production of such devices is part of the strategy of sustainable environmental development [9][10][11][12][13][14][15][16]. The most studied proton conductors are barium cerates-zirconates [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical devices such as proton-conducting fuel cells [1][2][3] and electrolyzers [4,5] are in dire need of highly efficient materials with targeted properties including proton conductivity [6][7][8]. Active development and implementation of these devices as a part of the "hydrogen energy in everyday life" strategy should ensure sustainable environmental development [9][10][11][12][13][14][15][16]. The electrolyte material of a hydrogen-powered electrochemical device must satisfy a number of requirements, including high proton conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of proton conductivity in bilayer AA′2B2O7 perovskites such as on BaLa2In2O7 [42][43][44], BaNd2In2O7 [45] and SrLa2Sc2O7 [46] and compositions based on them was described last year. It was shown that doping cationic sublattices can improve oxygen-ion and proton conductivity by up to 1.5 orders of magnitude [12]. It can be predicted that codoping can also promote an increase in conductivity.…”
Section: Introductionmentioning
confidence: 99%